2019
DOI: 10.3344/kjp.2019.32.4.307
|View full text |Cite
|
Sign up to set email alerts
|

New insights into pathways of the dorsal scapular nerve and artery for selective dorsal scapular nerve blockade

Abstract: BackgroundThe aim of this study was to clarify the topographical relationships between the dorsal scapular nerve (DSN) and the dorsal scapular artery (DSA) in the interscapular region to identify safe and convenient injection points related to DSN blockade.MethodsThirty shoulders of embalmed Korean cadavers and 50 live subjects were used for dissection and ultrasound (US) analysis.ResultsThe running patterns of the DSA and DSN in the interscapular region were classified into 3 types. Type I was defined as nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“… 28 The DSA, which is located medial to the superior angle of the scapula and on the first rib, was delineated in the short axis with the ultrasound probe; the beating was confirmed on the Doppler image; and then the probe was rotated to delineate the vessel in the long axis. In a prior study, the DSA was observed in 94% at this specific site, 5 and our study observed the DSA in all cases. The angle of incidence was set at 60°.…”
Section: Methodssupporting
confidence: 76%
“… 28 The DSA, which is located medial to the superior angle of the scapula and on the first rib, was delineated in the short axis with the ultrasound probe; the beating was confirmed on the Doppler image; and then the probe was rotated to delineate the vessel in the long axis. In a prior study, the DSA was observed in 94% at this specific site, 5 and our study observed the DSA in all cases. The angle of incidence was set at 60°.…”
Section: Methodssupporting
confidence: 76%
“…First, SNE syndrome has a variety of causes, including trauma, rotator cuff damages, repetitive overhead activities, and the supraspinatus and/or infraspinatus muscles. [20][21][22][23][24][25][26][27][28][29][30] However, we only focused on the infraspinatus muscle. Second, there may be incorrect measurements of IMCSA and SMT in MRS.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies can also be used for diagnosis [ 14 , 15 ]. Ultrasound, X-ray, computed tomography, and MRI provide information on the suprascapular nerve and surrounding structures, helping diagnose SNES [ 15 , 25 , 26 ]. Nerve conduction velocity and EMG are the gold standards for SNES diagnosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%